Factors Associated with the Competencies of Public Health Workers in Township Hospitals: A Cross-Sectional Survey in Chongqing Municipality, China - He, Zhifei (MDPI, 2015)
Purpose: This study aimed to explore the competencies of public health workers (PHWs) of township hospitals in Chongqing Municipality (China), and determine the related impact factors of the competencies of PHWs; Methods: A cross-sectional research was conducted on 314 PHWs from 27 township hospitals in three districts in Chongqing Municipality (China), from June to August 2014. A self-assessment questionnaire was established on the basis of literature reviews and a competency dictionary. The differences in competencies among the three districts were determined by adopting the chi-square test, t-test, analysis of variance (ANOVA) method, and the impact factors of the competencies of PHWs were determined by adopting stepwise regression analysis. Results: (1) Results of the demographic characteristics of PHWs in three sample districts of Chongqing Municipality showed that a significant difference in age of PHWs (p = 0.021 < 0.05) and the majors of PHWs (p = 0.045 < 0.05); (2) In terms of the self-evaluation competency results of PHWs in township hospitals, seven among the 11 aspects were found to have significant differences in the three districts by the ANOVA test; (3) By adopting the t-test and ANOVA method, results of the relationship between the characteristics of PHWs and their competency scores showed that significant differences were found in the economic level (p = 0.000 < 0.05), age (p = 0.000 < 0.05), years of working (p = 0.000 < 0.05) and title of PHWs (p = 0.000 < 0.05); (4) Stepwise regression analysis was used to determine the impact factors of the competencies of PHWs in township hospitals, including the economic level (p = 0.000 < 0.001), years of working (p = 0.000 < 0.001), title (p = 0.001 < 0.005), and public health major (p = 0.007 < 0.01). Conclusions: The competencies of the township hospital staff in Chongqing Municipality (China), are generally insufficient, therefore, regulating the medical education and training skills of PHWs is crucial to improve the competencies of PHWs in the township hospitals of Chongqing Municipality. The results of this study can be mirrored in other areas of China.